The Effect of Parenting Style on Athletes' Achievement Motivation - Prasetiyo, Rahayu; Maksum, Ali; Anung Priambodo (CV. Inara, 2021)
This study aims to determine the effect of parenting on the achievement motivation of athletes. The research method in this study is ex post facto. The sample in this study was as many as 73 athletes who are members of the East Java Regional Training Center. The instrument used was developed based on theoretical references regarding parenting patterns which consist of three types of parenting, namely authoritarian, authoritative and permissive with the results of factor analysis for each dimension of parenting parenting resulting in KMO-MSA values> 0.05 with a significance value of Bartlett's Test of Sphericity < 0.05. Each item in each dimension has a loading factor value > 0.5 so that each item is valid in measuring each dimension. While the achievement motivation instrument was also developed based on theoretical references with the results of factor analysis resulting in a KMO-MSA value> 0.05 with a significance value of Bartlett's Test of Sphericity <0.05. Test analysis using Analysis of Variance (ANOVA). Based on these calculations and criteria, the results (Sig.) 0.000 < 0.05, meaning that there is an influence of parenting style on athletes' achievement motivation. Judging from the mean value of authoritarian parenting is 10.37, authoritative parenting is 19.89, permissive parenting is 9.89. This means that authoritative parenting has the highest influence on athletes' achievement motivation. Then followed by authoritarian parenting in the second place and permissive parenting in the third or the last